Fungal Glucosylceramide-Specific Camelid Single Domain Antibodies Are Characterized by Broad Spectrum Antifungal Activity - De Coninck, Barbara; Verheesen, Peter; Vos, Christine M.; Van Daele, Inge; De Bolle, Miguel F.; Vieira, Joao V.; Peferoen, Marnix; Cammue, Bruno P. A.; Thevissen, Karin (Frontiers in Microbiology, 2017)
Chemical crop protection is widely used to control plant diseases. However, the adverse effects of pesticide use on human health and environment, resistance development and the impact of regulatory requirements on the crop protection market urges the agrochemical industry to explore innovative and alternative approaches. In that context, we demonstrate here the potential of camelid single domain antibodies (VHHs) generated against fungal glucosylceramides (fGlcCer), important pathogenicity factors. To this end, llamas were immunized with purified fGlcCer and a mixture of mycelium and spores of the fungus Botrytis cinerea, one of the most important plant pathogenic fungi. The llama immune repertoire was subsequently cloned in a phage display vector to generate a library with a diversity of at least 108 different clones. This library was incubated with fGlcCer to identify phages that bind to fGlcCer, and VHHs that specifically bound fGlcCer but not mammalian or plant-derived GlcCer were selected. They were shown to inhibit the growth of B. cinerea in vitro, with VHH 41D01 having the highest antifungal activity. Moreover, VHH 41D01 could reduce disease symptoms induced by B. cinerea when sprayed on tomato leaves. Based on all these data, anti-fGlcCer VHHs show the potential to be used as an alternative approach to combat fungal plant diseases.